The Sexualized Image of Soldaderas Using Propaganda from the Mexican Revolution: 1910-1920 - Mora, Jessica Yarissa; Martinez, Diana; Sanchez, Daisy (The Toro Historical Review, 2019)
The Mexican Revolution of 1910 was a war fought by rebels wanting to establish a democracy in Mexico after being ruled by a dictator for nearly 30 years. Once the country was fully in war and divided in two, women had only two choices. The first was to stay behind and struggle with finding food and earning money. Their other choice was to follow their men to battle and assist them with their needs on the battlefield. These women would cook, do laundry, acted as nurses for those wounded in battle, and would fight alongside the men on the battlefield when needed. This paper will explore the significant roles of soldaderas during the Mexican Revolution and how propaganda from the Mexican Revolution sexualized the image of soldaderas. The paper will also attempt to explain why were these women being romanticized for doing the same chores they had when they lived at home and why it was that both armies began getting rid of soldaderas from their ranks after having allowed their participation since the beginning of the war.